2016
DOI: 10.4172/2155-9589.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Asymmetric Ultrafiltration Membrane from Naturally Occurring Kaolin Clays: Application for the Cuttlefish Effluents Treatment

Abstract: This work concerns to the development and characterization of support and ultrafiltration membranes from naturally occurring-kaolin clays as principal components. The preparation and characterization of porous tubular supports, using kaolin powder with corn starch as poreforming agent, were reported. It has been found that the average pore size was about 1 μm while the pore volume was 44% for supports sintered at 1150°C with a flexural strength of about 15 MPa. The deposition of the active layer was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…The evolution of porosity as a function of sintering temperature (Table II) showed that G 2 sintered at 900 °C and G 3 sintered at 850 °C had the highest porosity (41%). Similar results were reported in the literature for the increase in porosity with an increase in the amount of the porogen [25][26].…”
Section: Resultssupporting
confidence: 91%
“…The evolution of porosity as a function of sintering temperature (Table II) showed that G 2 sintered at 900 °C and G 3 sintered at 850 °C had the highest porosity (41%). Similar results were reported in the literature for the increase in porosity with an increase in the amount of the porogen [25][26].…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that the membrane shows a better acid corrosion resistance, since its mass loss is much lower than those of membranes after alkali corrosion. Therefore, the observed results in weight loss during corrosion tests suggest that the prepared membrane possesses a good chemical corrosion resistance and it is suitable for applications involving acidic and basic media [42].…”
Section: Chemical Resistancementioning
confidence: 89%
“…The evolution of the average pore diameter and the porosity reveals that the porosity decreases from 44 to 27% between 1150°C and 1250°C, while the pore diameter increased from 0.41 to 0.73 µm. This behavior corresponds to an opening of the pores in the same time as a material densification occurring when the temperature increases [24,28,41,42].…”
Section: Mercury Porosimetrymentioning
confidence: 95%
“…The results obtained (Fig. 4) showed that there was a good porosity formed at the sintering temperature [45]. The beginning of the densification of the material occurred when the temperature increased [46][47][48][49].…”
Section: Resultsmentioning
confidence: 99%